Treatment as prevention for hepatitis C virus in Pakistan: mathematical modelling projections - Houssein H Ayoub (17704359) (2019)
Objective Direct-acting antivirals have opened an opportunity for controlling hepatitis C virus (HCV) infection in Pakistan, where 10% of the global infection burden is found. We aimed to evaluate the implications of five treatment programme scenarios for HCV treatment as prevention (HCV-TasP) in Pakistan. Design An age-structured mathematical model was used to evaluate programme impact using epidemiological and programme indicators. Setting Total Pakistan population. Participants Total Pakistan HCV-infected population. Interventions HCV treatment programme scenarios from 2018 up to 2030. Results By 2030 across the five HCV-TasP scenarios, 0.6–7.3 million treatments were administered, treatment coverage reached between 3.7% and 98.7%, prevalence of chronic infection reached 2.4%–0.03%, incidence reduction ranged between 41% and 99%, program-attributed reduction in incidence rate ranged between 7.2% and 98.5% and number of averted infections ranged between 126 221 and 750 547. Annual incidence rate reduction in the first decade of the programme was around 6%–18%. Number of treatments needed to prevent one new infection ranged between 4.7–9.8, at a drug cost of about US$900. Cost of the programme by 2030, in the most ambitious elimination scenario, reached US$708 million. Stipulated WHO target for 2030 cannot be accomplished without scaling up treatment to 490 000 per year, and maintaining it for a decade. Conclusion HCV-TasP is a highly impactful and potent approach to control Pakistan’s HCV epidemic and achieve elimination by 2030. Other Information Published in: BMJ Open License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1136/bmjopen-2018-026600